Effect of decreasing acidity on the extractability of inorganic soil phosphorus - Hartikainen, Helinä (Agricultural and Food Science, 1981)
The extractability of P by the water and anion exchange resin methods and reactions of soil inorganic P were investigated with seven acid mineral soil samples incubated with KOH solutions of various concentrations. The results were compared with the analytical data obtained from three soil samples incubated in a prolonged liming experiment. The resin extraction method proved more effective than the water extraction method. The amounts of P desorbed by both methods seemed to increase exponentially as the pH in the soil suspensions rose. The factors involved were discussed. On the basis of fractionation analyses P reacting to changes in the pH and participating in desorption processes was supposed to originate from secondary NH4F and NaOH soluble reserves. In general, as the acidity decreased NH4F-P increased at the expense of NaOH-P. In heavily limed gyttja soil also H2SO4-P increased. This was possibly induced by the precipitation of mobilized P as a Ca compound. The significance of pH in the extractability of soil P seemed somewhat to lessen as the amount of secondary P increased. The results were in accordance with the conception that liming improves the availability of inorganic P to plants and reduces the need for P fertilization. However, increasing of the soil pH involves the risk that P is more easily desorbed to the recipient water by the eroded soil material carried into the watercourse. Therefore, intensive liming is not recommendable close to the shoreline. Further, it should be taken into account that liming of lakes may also result in eutrophication as desorption of sedimentary inorganic P is enhanced.